2015
DOI: 10.1002/bio.2996
|View full text |Cite
|
Sign up to set email alerts
|

Binding of caffeine with caffeic acid and chlorogenic acid using fluorescence quenching, UV/vis and FTIR spectroscopic techniques

Abstract: The interactions of caffeine (CF) with chlorogenic acid (CGA) and caffeic acid (CFA) were investigated by fluorescence quenching, UV/vis and Fourier transform infrared (FTIR) spectroscopic techniques. The results of the study indicated that the fluorescence quenching between caffeine and hydroxycinnamic acids could be rationalized in terms of static quenching or the formation of non-fluorescent CF-CFA and CF-CGA complexes. From fluorescence quenching spectral analysis, the quenching constant (KSV), quenching r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…In the wavenumber range of 1,000–2,000 cm −1 , bare TiO 2 shows no discernable peaks. Caffeic acid showed several series of peaks in the 1,500–1,620 cm −1 range corresponding to C–C and C=C ring vibrations, a major peak at 1,148 cm −1 corresponding to aromatic C=C stretching, a peak at 1,641 cm −1 corresponding to acyclic C=C stretching and peaks in the 1,100–1,300 cm −1 corresponding to C–O stretching (Belay, Kim, & Hwang, 2016; Li, Wu, & Zhitomirsky, 2010; Wu et al, 2010). These peaks were also observed in the CA‐modified TiO 2 samples, which confirmed that CA molecules were indeed absorbed onto the surface of the TiO 2 NP.…”
Section: Resultsmentioning
confidence: 99%
“…In the wavenumber range of 1,000–2,000 cm −1 , bare TiO 2 shows no discernable peaks. Caffeic acid showed several series of peaks in the 1,500–1,620 cm −1 range corresponding to C–C and C=C ring vibrations, a major peak at 1,148 cm −1 corresponding to aromatic C=C stretching, a peak at 1,641 cm −1 corresponding to acyclic C=C stretching and peaks in the 1,100–1,300 cm −1 corresponding to C–O stretching (Belay, Kim, & Hwang, 2016; Li, Wu, & Zhitomirsky, 2010; Wu et al, 2010). These peaks were also observed in the CA‐modified TiO 2 samples, which confirmed that CA molecules were indeed absorbed onto the surface of the TiO 2 NP.…”
Section: Resultsmentioning
confidence: 99%
“…In the FTIR spectrum of CA, this phenolic acid was mostly characterized by its hydroxyl and carbonyl functional groups. One can observe the presence of two parallel peaks that correspond to the vibration of O-H group attached to the benzene ring centered at 1274 and 1214 cm −1 [57]. Furthermore, in the region from 1700 to 1600 cm −1 , the broad band with three intensities at 1642, 1618, and 1598 cm −1 was due to C=O stretching.…”
Section: Chemical Propertiesmentioning
confidence: 92%
“…27 CA is a natural phytochemical phenolic constituent in plants found in high concentrations in coffee, wine, and tea as well as in propolis. CA exhibits antioxidant and free radical scavenging properties, due to its rich chemical structure of phenolic-hydroxyls; 30,31 accordingly, it exhibits various biological functions, comprising antibacterial, anti-inflammatory, immunomodulatory, and anticancer activities. 32,33 Accordingly, ZnO NPs were conjugated with CA to prepare ZnO-CA NPs to improve their in vitro antitumor activity.…”
Section: •−mentioning
confidence: 99%